2007
DOI: 10.1159/000100929
|View full text |Cite
|
Sign up to set email alerts
|

Increased QT Dispersion in Sickle Cell Disease: Effect of Pulmonary Hypertension

Abstract: Background: QT dispersion has been proposed to be a predictor of adverse outcomes in a variety of cardiac disease states. The objective of this study was to examine QT dispersion in patients with sickle cell disease (SCD) and to assess the effect of pulmonary hypertension (PHT) on QT dispersion. Methods: We performed Doppler echocardiographic assessments of pulmonary artery systolic pressure in 73 (mean age 18.5 ± 8.0 years) steady-state SCD patients and 25 (mean age 19.6 ± 7.2 years) healthy subjects. Resting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 55 publications
4
26
1
Order By: Relevance
“…We studied the effect of pulmonary artery pressure measured by echocardiography and cardiac catheterization, and we found no significant effect of pulmonary artery pressure on QTc. These results disagree with Akgül et al [11] who determined that prolongation of QTc was observed in patients with pulmonary hypertension due to sickle cell anemia and Hong-liang et al [12] who found positive correlation between the mean pulmonary artery pressure and the duration of QTc. Also Ş ap et al investigated ventricular repolarization via QTc measurement in children with CHD and pulmonary hypertension.…”
Section: Discussioncontrasting
confidence: 69%
“…We studied the effect of pulmonary artery pressure measured by echocardiography and cardiac catheterization, and we found no significant effect of pulmonary artery pressure on QTc. These results disagree with Akgül et al [11] who determined that prolongation of QTc was observed in patients with pulmonary hypertension due to sickle cell anemia and Hong-liang et al [12] who found positive correlation between the mean pulmonary artery pressure and the duration of QTc. Also Ş ap et al investigated ventricular repolarization via QTc measurement in children with CHD and pulmonary hypertension.…”
Section: Discussioncontrasting
confidence: 69%
“…Also, they reported a positive correlation between pulmonary artery pressure and QTcd. In another study, Akgül et al found that among patients with sickle cell disease, those with [11]. Although, pulmonary hypertension developed acutely in our patients we also showed a positive correlation between pulmonary artery pressure and QTcd.…”
Section: Discussionsupporting
confidence: 61%
“…Several large prospective studies have reported QTd as a signifi cant prognostic factor in population with and without cardiac diseases [6][7][8]. Previous studies showed that chronic pulmonary hypertension is characterized with prolonged QT interval and increased QTd [9][10][11]. Also QT interval is reported to be prolonged in the acute phase of pulmonary embolism in high-risk patients, although its exact mechanism could not been explained.…”
Section: Introductionmentioning
confidence: 99%
“…Martin et al [17] found that QTc was prolonged (defined as ≥ 0.45 s) in two of 25 patients with right ventricular hypertrophy without other coexisting disorders but was not statistically significant in comparison with a normal control group. Akgül et al [14] found that among patients with sickle cell disease, those with PH had significantly higher mean QTc and QTcd than patients without PH. This is the only report of the effect of PH on QTc and QTcd; however, the patients all had sickle cell disease-induced PH.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that there are about 15,000 deaths annually in the USA alone from this disease [12]. It has been reported that QTcd is significantly increased in paoriginal article 331 tients with isolated right ventricular hypertrophy [13] and that QTc and QTcd are also significantly increased in sickle cell disease patients with PH in comparison with such patients without PH [14]. We hypothesize that QTc and QTcd are increased in patients with PH and are related to pulmonary pressure.…”
Section: Introductionmentioning
confidence: 88%